Recognition of Brain Metastases Using Gadolinium-Enhanced SWI MRI: Proof-of-Concept Study - Ceballos-Ceballos, Joel; Loza-Gallardo, Diego A.; Barajas-Romero, Marco A.; Cantú-Brito, Carlos; Valdés-Ferrer, Sergio Iván (Frontiers in Neurology, 2020)
Background and purpose: SWI MRI, a T2*-dominant MRI sequence with T1 shine-through effect, uses intrinsic structural susceptibility to create enhancement among brain structures. We evaluated whether gadolinium-enhanced SWI (SWI-Gd) improves brain metastasis detection in combination with other MRI sequences. Materials and methods: MRI images of 24 patients (46 studies) were prospectively acquired using a 1.5 T scanner. T1-weighted, unenhanced SWI (SWI-U), as well as SWI-Gd, were evaluated blindly to clinical features by two board-certified radiologists. Results: SWI-Gd revealed more significantly metastatic lesions than either T1-Gd or SWI-U (p=0.0004 for either comparator sequence). Moreover, SWI-Gd revealed more lesions when only those patients with ≤5 lesions on T1-Gd (n=30 studies from 16 patients; p=0.046). Performing SWI-Gd added less than five minutes of scanning time with no further additional risk. Conclusions: Our findings suggest that, when added to T1-Gd and other common sequences, SWI-Gd may improve the diagnostic yield of brain metastases with only a few extra minutes of scanning time and no further risk than that of a regular gadolinium-enhanced MRI.